Sistem Pengusiran Hama Burung Secara Otomatis Pada Lahan Pertanian Padi - inda, nur; Tria, Rahmi (Journal of System and Computer Engineering, 2025)
The importance of advancing sustainable rice farming is because rice is a staple food whose production must be increased to meet the basic needs of the community. The problem that occurs to rice farmers is that thousands of bird pests look for food in fertile rice fields, causing great losses for farmers. The way farmers efficiently repel bird pests is by developing technology that can monitor bird activity around rice fields in real time remotely and is able to repel bird pests by using the Internet Of Things (IoT) development. which aims to design IoT or tools that can monitor bird activity in real time around agricultural areas remotely, by utilizing PIR sensors to detect bird pests, LDR resistors detect light, ESP32-CAM to monitor rice fields and utilizing solar panel power as a sound signal generator that will sound disturbing the bird's hearing system so that the birds fly away and move the DC motor to repel bird pests automatically and the data collected from the ESP32-CAM (1) sensor will be sent to the IoT platform with the Telegram application connected via an internet connection, allowing farmers to monitor remotely via smart devices such as smartphones or computers.